2020
DOI: 10.1080/10508422.2020.1830404
|View full text |Cite
|
Sign up to set email alerts
|

The effects of emotion and social consensus on moral decision-making

Abstract: This study investigated the influence of different emotions and social consensus on moral decision-making using a mixed 2 (emotion: positive, negative) × 2 (social consensus: high, low) experimental design. The results showed that the main effect of social consensus was significant: the moral decision-making level of participants under the condition of low social consensus was lower than that of participants under the condition of high social consensus, while no main effect of emotion emerged. Second, the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Hume argued that since we cannot completely eradicate self-interest, it is better to transform the problem by providing an effective constraint than by the agreement concluded by all members of society, which is achieved through social interaction, a general sense of the common good manifested. Therefore, (Kay and Saucier, 2020) and that can influence moral decisions (Wang et al, 2021).…”
Section: Technology Moral Consensusmentioning
confidence: 99%
See 1 more Smart Citation
“…Hume argued that since we cannot completely eradicate self-interest, it is better to transform the problem by providing an effective constraint than by the agreement concluded by all members of society, which is achieved through social interaction, a general sense of the common good manifested. Therefore, (Kay and Saucier, 2020) and that can influence moral decisions (Wang et al, 2021).…”
Section: Technology Moral Consensusmentioning
confidence: 99%
“…Similarly, when people face the moral problems brought by technology, they also need to form moral consensus. With this dimension, we can capture not only what individuals think technology is moral, but also the moral consensus that society needs ( Kay and Saucier, 2020 ) and that can influence moral decisions ( Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that emotions can greatly impact individual attitudes and behaviors, especially decision-making (Lerner and Keltner, 2001 ; Li et al, 2011 ; Wang et al, 2021 ; Karen et al, 2022 ). A considerable amount of studies have shown that emotions can influence people's decision-making behaviors (Loewenstein and Lerner, 2003 ; Bechara and Damasio, 2005 ; Clore and Huntsinger, 2007 ; Sohn et al, 2015 ; Herman et al, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…16,17 Additionally, family members might be unable to fully process the information if their emotional distress has not been addressed. 18 As negative emotions are correlated with insomnia, 19 poor interpersonal relationship, 20 poor judgement 21 and extreme behaviours, 22 we believe that it is very important to identify negative emotions and explore an appropriate coping strategy in the context of poor doctor-patient relationships in China. Patients and their family members, who have inadequate medical knowledge, might experience more negative emotions when confronting decisions on critical health issues such as cancer diagnosis, treatment options and major operations with high risks.…”
Section: Introductionmentioning
confidence: 99%